Researches regarding the consumption of grapes and wine in Romania - Petruţa Antoneta Enache (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
Viticulture in Romania is a traditional activity, harmoniously developed as a result of the extremely favourable natural conditions that grapevine encounters throughout the country. Viticulture has always taken an important spot in the agricultural economy on a national level as well as worldwide, being appreciated from several points of view like: social (nutrition sources: grapes, wine, traditional products that come from them) and economic (viticulture products capitalization, internal commerce, international commerce). Education, viticulture tourism and socio-economic development in the last years have left their mark upon the consumption of grapes and grapes products by Romanian consumers. The consumption and choosing of products has become a more and more documented activity for Romanians. The purpose of this study is to follow the evolution of grapes and wine consumption in Romania with the help of statistic indicators. By analyzing future perspectives regarding consumption on a national level it is expected that by 2025 the average annual grapes consumption will surpass 23 kg/inhabitant, if it maintains the same tendency from the analyzed period. In order to develop this sector, a series of financial aids and support measures have been extended in order for the farmers to benefit from.
Keywords: Q10; Q11; Q18; 330; grapes; wine; wine products; consumption